2011
DOI: 10.1073/pnas.1016088108
|View full text |Cite
|
Sign up to set email alerts
|

Short-chain fatty acids and ketones directly regulate sympathetic nervous system via G protein-coupled receptor 41 (GPR41)

Abstract: The maintenance of energy homeostasis is essential for life, and its dysregulation leads to a variety of metabolic disorders. Under a fed condition, mammals use glucose as the main metabolic fuel, and short-chain fatty acids (SCFAs) produced by the colonic bacterial fermentation of dietary fiber also contribute a significant proportion of daily energy requirement. Under ketogenic conditions such as starvation and diabetes, ketone bodies produced in the liver from fatty acids are used as the main energy sources… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
767
3
8

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 880 publications
(846 citation statements)
references
References 41 publications
18
767
3
8
Order By: Relevance
“…Both FFAR2 and FFAR3 are activated by physiological concentrations of SCFA, although a preference of FFAR2 for acetate and propionate and of FFAR3 for propionate and butyrate has been reported (29)(30)(31) . These receptors have been shown to be expressed not only in the gut epithelium (32,33) where SCFA are produced and are at their highest concentrations, but also at multiple tissue sites, including adipose tissue (34)(35)(36) , immune cells (29) , skeletal muscle (31) and within the peripheral nervous system (37,38) . A possible role for these receptors in energy intake regulation emerged with the identification that FFAR2 and FFAR3 are present on colonic endocrine L-cells (32,33) .…”
Section: Scfa Receptors and Anorectic Gut Hormone Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Both FFAR2 and FFAR3 are activated by physiological concentrations of SCFA, although a preference of FFAR2 for acetate and propionate and of FFAR3 for propionate and butyrate has been reported (29)(30)(31) . These receptors have been shown to be expressed not only in the gut epithelium (32,33) where SCFA are produced and are at their highest concentrations, but also at multiple tissue sites, including adipose tissue (34)(35)(36) , immune cells (29) , skeletal muscle (31) and within the peripheral nervous system (37,38) . A possible role for these receptors in energy intake regulation emerged with the identification that FFAR2 and FFAR3 are present on colonic endocrine L-cells (32,33) .…”
Section: Scfa Receptors and Anorectic Gut Hormone Releasementioning
confidence: 99%
“…Furthermore, it was found in vivo that elevating circulating levels of propionate increased leptin levels in mice. Nevertheless, not all researchers have been able to detect FFAR3 in different adipose tissue sites (34,36,37) , thus the role of FFAR3 in adipose tissue function is currently a contentious topic. It has been …”
Section: Scfa and Leptin Secretionmentioning
confidence: 99%
“…72,73 SCFAs can also directly activate the sympathetic nervous system through Gpr41 receptors that are found on sympathetic ganglionic neurons. 74 Furthermore, it has been shown that SCFAc can pass through the blood-brain barrier and influence behavior, neural signaling, the production of neurotransmitters and, ultimately, behavior. [75][76][77] Change in Central Nervous System Neurotransmitters Studies have reported on CNS neurotransmitter changes in response to more specific biological factors that may be restricted to certain types of bacteria, thus providing a mechanistic link to changes in microbial metabolism.…”
Section: Effect Of Bacterial Metabolites On the Central Nervous Systemmentioning
confidence: 99%
“…The administration of prebiotics also stimulates the production of SCFA which may modulate the secretion of gut peptides (Brown et al 2003;Ge et al 2008;Samuel et al 2008;Kimura et al 2011). Prebiotics may exert a satietogenic effect as demonstrated and confirmed in studies with mice in which the effects of acetate on production of appetite suppression were shown, even in absence of increased levels of GLP-1 and PYY (Frost et al 2014).…”
Section: Prebioticsmentioning
confidence: 99%